Ameliorative Effect of Chitosan Complex on Miniature Pig Sperm Cryopreservation - Hye-Min Hong; Ga-Young Sim; So-Mi Park; Eun-Joo Lee; Dae-Young Kim (The Korean Society of Animal Reproduction and Biotechnology, 2018)
Cryopreservation is mainly used for preservation of boar sperm. However, this method stresses the sperm by reactive oxygen species (ROS), and the conception rate and the litter size are not more efficient than the liquid preservation of spermatozoa. Therefore, we use chitosan which is a natural product derived antioxidant compound. We used GnHA (chitosan+hyaluronic acid) and GnHG (chitosan hydrogel) as chitosan complexes to cryopreserve boar sperm for improve sperm metabolism and function. Sperm parameter (sperm motility, progressive motility, path velocity, straight-line velocity, curvilinear velocity) is measured by computer-assisted sperm analysis (CASA) using frozen sperm with GnHA or GnHG (0, 0.25, 0.5, 1 mg/mL), respectively. Also, lipid peroxidation analysis using malondialdehyde (MDA) is performed to confirm the antioxidative effect of chitosan in frozen spermatozoa. CASA analysis showed GnHA and GnHG are effective against cryopreserved boar sperm. And antioxidant effect is measured by lipid peroxidation analysis. GnHA and GnHG, which is chitosan complex are effective for boar sperm cryopreservation by antioxidant effect.